Synthesis, Characterization, and Biological Evaluation of Some Novel Phthalimide Derivatives: Synthesis, Characterization, and Biological Evaluation of Some Novel Phthalimide Derivatives - Maity, Tapan Kumar (International Journal of Pharmaceutical & Biological Archive, 2019)
Objective: Different Phthalimide derivatives (4,5,6,7-tetrachloro-2-[1,2,4]triazol-4-yl]-isoindole-1,3-dione derivatives) were synthesized and biological activities of them were evaluated. Materials and Methods: In the present study, four new phthalimide derivatives were synthesized. The structures of final compounds were characterized on the basis of spectral data. Then, biological evaluation of all the synthesized compounds means in vivo anticancer activity was evaluated on the Ehrlich ascites carcinoma (EAC) bearing Swiss albino mice model, and in vitro antioxidant activity was assessed using 1,1-diphenyl-2-picryl hydrazine (DPPH) radical scavenging assay. Results: The titled compounds (2A-2D) were found to reduce tumor volume, viable cell count and increase non-viable cell count, and percentage increase in life span. All compounds showed significant activity in quenching DPPH free radical. Conclusion: All compounds showed significant (P<0.01) anticancer activity compared to EAC control group. All synthesized compound exhibited considerable antioxidant activity against free radicals, and they showed significant IC50 values and can, thus, ensure protection against oxidative stress.